Visual Hallucination, Visual Evoked Potentials and Cognitive Dysfunction in Idiopathic Parkinson’s Disease - Tuba Aydemir Özcan; Feriha Özer; Hürtan Acar; Sibel Çetin; Serkan Özben; Gülsün Çınarlı Gül (Türk Nöroloji Dergisi, 2011)
OBJECTIVE: In this study, we aimed to investigate the relation between possible visual evoked potentials (VEP) pathologies and visual hallucinations (VH) seen in idiopathic Parkinson’s disease (IPD) and the role of cognitive dysfunctions in VHs, moving through visual processing defect considered to be related to VHs could be demonstrated with VEP to some extent. METHODS: Two groups followed in the Movement Disorders outpatient clinic of Haseki Training and Research Hospital were included in our study. Group 1 included 14 IPD patients with VH and a mean age of 65.31 ± 7.49 years, while Group 2 (as control group) included 12 IPD patients without VH and a mean age of 68.17 ± 7.46 years. RESULTS: : While dosage of levodopa was found to be significantly higher in the group with VH (p= 0.048), it was observed that Unified Parkinson's Disease Rating Scale (UPDRS) cognitive scores were also significantly greater in this group (p< 0.001). No difference was observed between the two groups regarding the rate of pathological VEP latency (p= 0.64). In our study, Stroop Color-Word Test, among other executive functioning tests, was statistically significantly worse for duration/error in the group with VH (p= 0.016/0.003). CONCLUSION: In Group 1, VEP results may have been worse due to the higher dosage of levodopa and higher UPDRS cognitive scores. VEP studies before and after dopaminergic therapy may be useful to understand the contribution of VEP investigations on the etiopathogenesis of VHs in IPD